O capital intelectual e a geração de valor no mercado de jogadores de futebol - Lopes Filho, Leonardo Luiz (2021)
Football is a renowned sport in the world that overflows the barriers of entertainment. When it comes to transactions, Brazil was the most participatory country in the transfer of international players. Football generated about 5.63 billion dollars in 2020, of which 734 million in transactions by Brazilian players (MUNDIM, 2021). Despite the emotions that revolve around this market, clubs are traditional institutions that have as their particularity the main characters of their successes, their intangible assets, that is, their players. Few Brazilian clubs have the financial conditions to make large financial investments since most of them have a low and inefficient degree of management professionalization, as well as very high debts (GIOVANNETTI; ROCHA; SANCHES; SILVA, 2006). In contrast, the intangible assets of these clubs - the players - have a high profit potential with great capacity to generate wealth that can be used as an escape valve for clubs to improve their financial situation. The objective of this master's dissertation is to analyze the determinants of the market values of the 500 most valued Brazilian soccer players using the intellectual capital indicators as explanatory variables. The database comes from the transfermarket website. The transfermarket is a British site, whose duties include determining the market values of athletes, and is constantly used in international sports journals. Descriptive statistics and panel data model estimates were used in the analyzes to control the player's fixed effects, the club's fixed effects and the effects of player-year and club-year interactions. The results found allow us to indicate that: (i) variables related to human capital (games played in the year, games for the selection and individual titles received by the player) contribute to increase the player's market value; (ii) The value of the club (structural capital) indicates that playing in a high value-added club contributes to increasing the player's market value. We concluded that the market value of soccer players is determined by a set of variables that can be explained by components of human capital (skills of the individual), structural capital (infrastructure that supports human capital) and relational capital ( ability of the individual to relate). Understanding pricing can help clubs improve their management and increase the possibility of financial success, since player transfers are the second main source of income for clubs and are second only to transmission quotas.